DIFFERENTIAL RESPONSE OF TROPICAL, TEMPERATE, AND TEMPERATE × TROPICAL MAIZE HYBRIDS IN YIELD AND STARCH CONTENT TO ENVIRONMENTAL VARIABILITY IN CHACO PROVINCE - Galvão, Frederico Ribeiro; Brandão, Heloanny de Freitas; Favaretto, José Eduardo Ricciardi (Seven Editora, 2026)
Chaco Province (Argentina) is characterized by extensive arable land and marked environmental heterogeneity, which directly impact productive development and enable high maize production levels. Although previous studies have compared average yields among hybrids, understanding the response of different genetic groups to environmental variability remains essential. This study analyzed the differential response in grain yield and starch content of tropical, temperate × tropical, and temperate maize hybrids grown across different locations in the province, considering edaphic and climatic conditions based on previously published data. Results indicated that the temperate group achieved the highest average grain yield (82.20 qq/ha) and a high starch content (73.48%), although its performance varied depending on environmental conditions. The tropical group showed a lower average grain yield (70.71 qq/ha) but exhibited differential responses, particularly in environments with variations in precipitation and soil type. Overall, the results suggest that hybrid selection should not rely solely on average yield but also on adaptation to specific environmental conditions. Environmental factors such as precipitation (308–820 mm) and soil characteristics (organic matter: 0.40–1.50%) influenced the expression of the genetic potential of each group. It is concluded that a significant interaction exists between genetic group and environment, which is critical for the recommendation of hybrid materials across the different productive subregions of Chaco.